Economic Dynamics of Muslim Households in the Childfree Phenomenon: An Islamic Financial Planning Perspective - Almizan Almizan; Erizal Candra Efendi; Wildan Hadi; Ruri Mustika (MARGIN ECO, 2026)
This study analyzes the economic dynamics of Muslim households involved in the childfree phenomenon from the perspective of Islamic financial planning. Using a qualitative phenomenological approach, data were collected through in-depth interviews with Muslim couples who voluntarily chose not to have children. The findings show that rising living costs, economic uncertainty, and career priorities significantly influence childfree decisions among Muslim households. Participants implemented Islamic financial planning practices such as savings, halal investment, retirement preparation, zakat, and controlled consumption to maintain household stability and long-term financial security. The study also reveals that family welfare is interpreted through emotional stability, marital harmony, psychological well-being, and financial balance rather than solely through parenthood. Furthermore, participants viewed childfree decisions as part of responsible household management aligned with Islamic principles of maslahah and household capability. This research contributes to discussions on Islamic household economics, fertility behavior, and contemporary Muslim family transformation.